2014
DOI: 10.18433/j3n590
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the C-type Lectins-Mediated Host-Pathogen Interactions with Dextran

Abstract: Dextran, the α-1,6-linked glucose polymer widely used in biology and medicine, promises new applications. Linear dextran applied as a blood plasma substitute demonstrates a high rate of biocompatibility. Dextran is present in foods, drugs, and vaccines and in most cases is applied as a biologically inert substance. In this review we analyze dextran’s cellular uptake principles, receptor specificity and, therefore, its ability to interfere with pathogen–lectin interactions: a promising basis for new antimicrobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
73
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 191 publications
(120 reference statements)
0
73
0
Order By: Relevance
“…Many potential DC-SIGN inhibitors are in various stages of research, [13][14][15] and approaches for the high-throughput screening of potential inhibitors are being developed. 37 Our earlier studies on human macrophages 38 demonstrate that dextrans are also inhibitors of the interaction of HIV with another C-type lectin MR (CD206). This latter receptor binds HIV on the surface of macrophages, also allowing them to transinfect the T cells, 39 and mediates the HIV infection of brain macrophages.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Many potential DC-SIGN inhibitors are in various stages of research, [13][14][15] and approaches for the high-throughput screening of potential inhibitors are being developed. 37 Our earlier studies on human macrophages 38 demonstrate that dextrans are also inhibitors of the interaction of HIV with another C-type lectin MR (CD206). This latter receptor binds HIV on the surface of macrophages, also allowing them to transinfect the T cells, 39 and mediates the HIV infection of brain macrophages.…”
mentioning
confidence: 99%
“…In addition, it has not been demonstrated that oligosaccharides with the linear dextran structure (a-1,6-linked glucose units) bind DC-SIGN. 17 Hence, we proposed to utilize the dextran molecule, as it is part of several injectable drug formulations that have a proven safety record, as an inhibitor of pathogen interaction with a set of C-type lectins including DC-SIGN (CD209) and mannose receptor (CD206). 17 In addition, we tested whether peptide triazoles could inhibit DC-SIGN-mediated HIV infection.…”
mentioning
confidence: 99%
See 3 more Smart Citations